Functional outcomes and quality of life after surgical treatment of spinopelvic dissociation: a case series with one-year follow-up - Giedrius Petryla (BMC Musculoskeletal Disorders, 2021)
Abstract Background Spinopelvic dissociation is a transverse sacral fracture in conjunction with a vertical fracture of the sacrum on both sides, which causes the dissociation of the upper sacrum and spine from the pelvis. The most common causes of these fractures are high energy injuries such as falls from height or motor vehicle accidents. Spinopelvic dissociation is rare and heterogenous with severe associated injuries. The aim of this study was to assess the injury characteristics, changes in the quality of life and functional outcomes in the 1-year period after spinopelvic dissociation. Materials and methods During the period of 4 years (January 2016 and January 2020), 17 patients with spinopelvic dissociation were admitted to our centre and included in this single-centre prospective cohort study. One patient died during the admission; therefore 16 patients were enrolled in the analysis. Patients were followed-up for 12 months. The quality of life changes were evaluated via the SF-36 questionnaire, and the functional outcomes were evaluated using the Majeed pelvic score. Patients completed their questionnaires twice: firstly during hospitalization (regarding their pre-traumatic condition); and once again 1 year after their injury (regarding their current condition). Results The mean age of the patients was 40.2 ± 17.7 years. Mean Majeed, PCS and MCS scores of SF-36 before the injury were 95.81 ± 9.50, 55.87 ± 8.89, and 43.76 ± 12.45, respectively. Mean Majeed, PCS and MCS scores 1 year after the injury were 71.13 ± 20.98, 43.45 ± 9.64, and 43.41 ± 7.56. During the period of 1 year after the injury, Majeed and PCS results reduced statistically significantly (P = 0.001 and P = 0.003, respectively), while MCS results remained similar (P = 0.501). Conclusions According to the data of our study, for patients with spinopelvic dissociation functional outcomes are significantly reduced and only one-third of the patients achieved pre-traumatic functional outcomes 1 year after the injury.